Requirements for developing high temperature creep life models for ageing pipework systems using power plant condition monitoring and inspection data. (December 2020) - Bonetti, R.; Morris, A.; Shipway, P.H.; Sun, W.
Abstract: A novel creep life assessment methodology is proposed in this paper that uses periodic and routine inspection data in conjunction with online operational data and other computed parameters, such as the 'rate of change', and where applicable correlations with data from small specimen tests on ex-service materials. The proposed methodology is critically implemented by the introduction of a life assessment transfer function (LATF). This enables the computation of the residual life of high temperature components and essentially links the plant data routinely collected during outage inspections, via online monitoring or by testing of material samples to the life prediction model. The LATF performs the function of data filtering, pre-conditioning and parameter derivation so that this information can be used effectively in the life prediction model. In this paper high temperature pipework is used as an example of the proposed approach and deployable creep life prediction models are reviewed that could function with these plant datasets and enabled by a suitable LATF. Of critical importance is that the output from the life prediction is used to inform plant operations on any necessary changes in order to mitigate damage accumulation. An example is provided to illustrate the current assessment approach, exploiting real inspection data for estimation of residual life, as well as how the proposed new approach will address the limitations. Highlights: A novel creep life assessment methodology is proposed in this paper using periodic and routine inspection data, online operational data, other computed parameters, and where applicable correlations with data from small specimen tests on ex-service materials. The life assessement transfer functionenables the computation of the residual life of high temperature components and links the plant data routinely collected during outage inspections with online monitoringl. The life assessment transfer function performs data filtering, pre-conditioning and parameter derivation.. High temperature pipework is used as an example of the proposed approach and deployable creep life prediction models are reviewed.. An example is provided to illustrate the current assessment approach, exploiting real inspection data for estimation of residual life, as well as how the proposed new approach will address the limitations and inform the operator.